The afterlives of war in Ishmael Beah's, radiance of tomorrow - Muriuki, Eva Wangari (My University, 2018)
This study was conceived and developed with the intention of initiating a discussion around post-war life in African literature and how this portrayed through realistic fiction writing. Ishmael Beah in his novel, Radiance of Tomorrow, aims to tackle several issues around neocolonialism, orality, tradition and development. My aim in this study is to analyze the ways in which Beah uses literature to communicate a larger message of post-war life obstacles. Following his widely received memoir, A Long Way Gone, Beah wanted to tell a less romanticized story of what life really looks like after the war. Beah makes use of several literary techniques in unique ways that go against their conventional literary uses. He makes use of irony to illustrate the negativity of irony, but does not use humor or satire. He uses personification to humanize the environment to portray how the people and the environment around them are one. He makes use of oral literature to portray the distorted histories that are being formed in order for the future generation to be shielded from the memories of war. This study seeks to add to the current literature on culture and post-war development, while working with ecocritical theories to explain the personification of the environment in the novel. With a close reading and analysis of the novel, as well as secondary readings from scholars who deal with trauma, literary devices and post-war literature, I hope to understand how Beah uses these different literary devices, how he chooses to organize his novel and most importantly, why.
A research report submitted in partial fulfilment for the Degree of Master of Arts In the Department of African Literature University of the Witwatersrand